SIGLEC11 promotes M2 macrophage polarization through AKT–mTOR signaling and facilitates the progression of gastric cancer - Chen Li; Yang Lu; Yihao Liu; Minmin Shi; Zhenggang Zhu; Jingxin Yin; Qimeng Shi; Da Fu; Zhenqiang Wang (Journal for ImmunoTherapy of Cancer)
Background Sialic acid-binding immunoglobulin-like lectins (SIGLECs) are widely expressed on immune cell surfaces, play an important role in maintaining immune homeostasis and regulating inflammatory responses, and are increasingly emerging as potential targets for tumor immunotherapy. However, the expression profile and crucial role of SIGLEC11 in gastric cancer (GC) remain unclear. This study aimed to elucidate the prognostic relevance of SIGLEC11 expression and its role in the immune microenvironment in patients with GC.Methods SIGLEC11 expression profile was analyzed using bioinformatics, immunohistochemistry, and immunofluorescence staining. Flow cytometry, mouse tumor models, patient-derived tumor organoid models, and RNA sequencing were used to explore the potential functions with the underlying mechanisms of SIGLEC11 in a coculture system of macrophages and GC cells.Results We demonstrated that SIGLEC11 was predominantly expressed in normal tissues. However, tumor-infiltrating SIGLEC11+ cells in the high SIGLEC11 expression subgroups showed poor overall survival, which was associated with the expression of an immunosuppressive regulator. Our results showed that SIGLEC11 was predominantly expressed in monocytes and macrophages and selectively upregulated in tumor-associated macrophages. Furthermore, SIGLEC11 promoted macrophage M2 polarization via AKT–mTOR signaling. In addition, SIGLEC11+ macrophages accelerate GC progression.Conclusions The abundance of SIGLEC11+ M2-like macrophage-infiltrating tumors may serve as a biomarker for identifying immunosuppressive subtypes of GC. Thus, the potential role of SIGLEC11+ M2 macrophages as therapeutic targets warrants further investigation.